New Nuclear Power Industry Procurement Markets: International Experiences - Ilchong Nam; Geoffrey Rothwell (Korea Development Institute (KDI), 2014)
Ensuring safety and efficiency of the procurement market for nuclear power generation has become one of the top priorities of the policy makers in Korea since the discovery of a large number of fraudulent parts and components used by nuclear power plants. This book analyzes the nuclear power industry procurement in Korea, France, and the UK. Although all three countries restructured their electricity industry, they differ substantially in the history of the nuclear power industry, ownership and governance of firms in the industry, and relevant legal infrastructure. The findings of this book will shed light on the factors that affect safety and efficiency in the nuclear power procurement markets and the right direction for reform.
Keywords: 330